2008
DOI: 10.1007/s00439-008-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of common genetic variants that account for transcript isoform variation between human populations

Abstract: In addition to the differences between populations in transcriptional and translational regulation of genes, alternative pre-mRNA splicing (AS) is also likely to play an important role in regulating gene expression and generating variation in mRNA and protein isoforms. Recently, the genetic contribution to transcript isoform variation has been reported in individuals of recent European descent. We report here results of an investigation of the differences in AS patterns between human populations. AS patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 53 publications
0
90
0
Order By: Relevance
“…Earlier studies have shown that common genetic variants contribute significantly to the individual differences in proteincoding gene expression variation (Cheung et al 2003(Cheung et al , 2005Morley et al 2004;Deutsch et al 2005;Stranger et al 2005Stranger et al , 2007Spielman et al 2007;Storey et al 2007) and transcript isoform variation (Hull et al 2007;Kwan et al 2007Kwan et al , 2008Zhang et al 2009). Our study adds a level of complexity to cellular gene expression regulation by revealing that cis-and trans-eQTLs can affect the expression of miRNAs that are themselves regulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that common genetic variants contribute significantly to the individual differences in proteincoding gene expression variation (Cheung et al 2003(Cheung et al , 2005Morley et al 2004;Deutsch et al 2005;Stranger et al 2005Stranger et al , 2007Spielman et al 2007;Storey et al 2007) and transcript isoform variation (Hull et al 2007;Kwan et al 2007Kwan et al , 2008Zhang et al 2009). Our study adds a level of complexity to cellular gene expression regulation by revealing that cis-and trans-eQTLs can affect the expression of miRNAs that are themselves regulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…1000genomes.org), with the most detailed catalog of human genetic variation, are emerging on the 270 HapMap LCLs. In addition, basal gene expression data are available for a portion of the 270 LCLs from Affymetrix Focus array (Spielman et al, 2007;Storey et al, 2007), Affymetrix Human Exon 1.0 ST array (exon array) Zhang et al, 2009), and Illumina BeadChips (Stranger et al, 2007a,b). Thus, with genotypic and expression data, the HapMap LCLs are a rich resource that requires only pharmacological phenotyping to evaluate genotype-phenotype, expression-phenotype, or genotype-expression-phenotype relationships.…”
Section: Application Of Lymphoblastoid Cell Line Models In Pharmacogementioning
confidence: 99%
“…All exons of TCF7L2 were sequenced in multiple patients and controls but no coding variation was identified [6] suggesting that T2DM risk is associated with a non-coding variation. Genetic variations may affect levels of expression and splicing architecture of mRNA transcripts [21] [22] thus several studies have tested the relationships between TCF7L2 mRNA expression and genotypes of rs7903146 and rs12255372 in human tissues [23] [24].…”
Section: Introductionmentioning
confidence: 99%